Strategy Intervention to Prevent and Reduce Postpartum Depression: A Systematic Review - M. Elyas Arif Budiman; Supiah Ningsih Juita Sari; Winda Kusumawardani; Dhona Sutopo (Universitas Airlangga, 2019)
Background: Postpartum depression is a non-psychotic depressive disorder with the criteria for diagnosis being that it can start early at four weeks postpartum. This can occur in the first year postpartum. Postpartum depression can result in deep sorrow and even the risk of suicide.Method: The sources of the articles used were from a search of the Scopus, PubMed and Proquest databases with the keywords “postpartum depression, nursing intervention, psychology and postpartum”. The search was restricted articles ranging from 2014 until 2018. After the articles were obtained, then the articles were reviewed until the stage of making a systematic review.Result: The systematic review resulted in 15 of 19 choices of interventions that can be used to prevent and reduce the symptoms of postpartum depression. The results found that an internet cognitive behavior therapy intervention is very significant in terms of preventing and reducing the symptoms of postpartum depression. Nursing interventions are packaged in a variety of programs proven to reduce the postpartum depression variables and actions needed to prevent and reduce the symptoms of postpartum depression significantly.Conclusion: Based on the results of the analysis of the 15 journals from the results of the study, internet cognitive behavior therapy intervention is recommended to prevent and reduce postpartum depression. This intervention can be developed practically and easily.